Semantic features of Bulgarian sentences of consequence and their Italian equivalents - Davidova, Desislava (Yearbook of the Department of Foreign Languages and Cultures, 2024)
The article attempts a semantic analysis of consequence constructions expressing cause-effect relationships through a bilingual translation corpus from Bulgarian into Italian. For Bulgarian, a semantic classification of consequence clauses is proposed, which is missing in the Bulgarian literature on grammar. The logic inherent in the cause-effect relationships determines their division into two types, which is the aim of the functional-semantic analysis, namely to show the extent to which this logical relationship is present in each type. The conclusions from the analysis show a clear difference at the syntactic and semantic level between intensive-resultative and constative-resultative consequence clauses. In the first type of clauses, even in cases of complicated syntax with more than one subordinate clause, the intensity-result relation is preserved. In the second type though, the logical relation between cause and effect is weakened, allowing the context to become the determining factor and not the typical logic inherent in cause-effect relationships. As a result, the translation shows a preference for conjunctions, concluding adverbs, with which the subordinate clause of consequence can be separated from the main one and thus can function as a simple sentence.